Artificial Intelligence Based Al-Qur'an Learning Media Design “Tarteel” on Fastabiqul Khoirot Material - Eka Rohmatun Nazilah; Nadia Fatchu Ilmi (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
This study discusses the design of artificial intelligence-based Al-Qur'an learning media through the Tahseen platform with a focus on the theme of Fastabiqul Khoirot. Al-Qur'an learning in the digital era faces challenges in the form of a lack of interest and involvement of students due to monotonous conventional methods. This study, through library research, aims to provide an overview of how to increase the efficiency of Al-Qur'an learning by integrating AI "Tarteel" Fastabiqul Khoirot Material in the learning process. This study considers the ethical and practical implications of the use of AI technology in religious learning and evaluates its impact on Al-Qur'an learning. In addition, this study also identifies various opportunities and challenges in the use of AI. The results of the study show that the AI “Tarteel” Fastabiqul Khoirot Material not only functions as a supplementary learning medium, but also proven effective in helping students improve their basic Quran reading skills. This success supports the use of applications as innovative learning solutions, while also confirming that technology-based learning, such as the Tarteel application, has great potential to be further developed to improve the quality of Quran education for all students . It is hoped that the results of this study can encourage wider adoption of AI technology in the education system, especially in the context of Quran learning. By strengthening the understanding of how best to utilize AI technology in Quran learning, it is hoped that a more effective and holistic approach can be developed.